2002
DOI: 10.3171/foc.2002.12.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Single enhancing computerized tomography–detected lesion in immunocompetent patients

Abstract: Single enhancing computerized tomography (CT)–documented lesions may occur in several infectious and neoplastic diseases of the central nervous system and are the most common radiological abnormality seen in patients with acute-onset seizures in India and many other developing countries. Similar CT-documented lesions have also been reported in the developed world where these lesions are often considered to be caused by neoplasms or tuberculoma. Histopathological studies in India and even in some develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
14
0
3
Order By: Relevance
“…[165][166][167] In Latin America, the proportion of NCC patients with a single-enhancing lesion varies from 3.5 to 34%, 168 likely reflecting different definitions of a single-enhancing lesion. More importantly, other infections, tumors, vascular lesions, and other etiologies need to be considered in the differential diagnosis of single brain lesions, [168][169][170] and thus serology could be of great help in saving unnecessary invasive procedures or treatments. 171 In general, all immunodiagnostic tests show low sensitivity for the diagnosis of single-lesional NCC, even worse when the lesion has entered in an involutive, degenerative process of resolution following antiparasitic treatment or by natural evolution ('single-enhancing lesion' or single cysticercal granuloma').…”
Section: Single-lesional Nccmentioning
confidence: 99%
“…[165][166][167] In Latin America, the proportion of NCC patients with a single-enhancing lesion varies from 3.5 to 34%, 168 likely reflecting different definitions of a single-enhancing lesion. More importantly, other infections, tumors, vascular lesions, and other etiologies need to be considered in the differential diagnosis of single brain lesions, [168][169][170] and thus serology could be of great help in saving unnecessary invasive procedures or treatments. 171 In general, all immunodiagnostic tests show low sensitivity for the diagnosis of single-lesional NCC, even worse when the lesion has entered in an involutive, degenerative process of resolution following antiparasitic treatment or by natural evolution ('single-enhancing lesion' or single cysticercal granuloma').…”
Section: Single-lesional Nccmentioning
confidence: 99%
“…Although CT and conventional MRI findings have been described for the diagnosis of tuberculomas and tuberculous abscess, these are non-specific characteristics of the disease in a number of patients. Tuberculomas and tuberculous abscess constitute approximately 10 to 20% of all intracranial masses: a single enhancing CT documented lesion may occur in several CNS infectious and neoplastic diseases and is the most common radiological abnormality seen in patients with acuteonset seizures [14] .…”
Section: Resultsmentioning
confidence: 99%
“…The rate of disappearance of lesion has ranged from 22 to 100% at 12 weeks after detection 14 . In a prospective study of 210 patients, Rajshekhar et al 15 observed that at 3 months only 19% of lesion had completely resolved; at 1 year approximately 63% had disappeared.…”
Section: Radiological Outcomementioning
confidence: 99%